Groundwater chemical baseline values to assess the Recovery Plan in the Matanza-Riachuelo River basin, Argentina - Zabala, Maria Emilia (2016)
The two most exploited aquifers in the Matanza-Riachuelo River basin are being monitored in the framework of the Integrated Environmental Sanitation Plan that implements the Basin Authority, Autoridad de Cuenca Matanza Riachuelo. In this context, this work identifies the groundwater chemical types and the natural processes behind them; determines spatial and temporal changes; establishes ranges of variation for chemical components, and proposes concentration values for the upper limit of the natural chemical background. A total of 1007 samples from three aquifer-layers (Upper Aquifer, top and bottom of Puelche Aquifer) have been studied. As concrete guidelines for practical determination of baseline values are not available in the region, the methodology used follows the proposals of European projects which assessed European water directives. The groundwater composition is very stable in terms of both chemical facies and mineralization degree, and the changes observed in the dry and wet periods analysed are subtle in general. Most of the groundwater is Na-HCO3 type, except a few samples that are Ca-HCO3, Na-ClSO4 and Na-Cl types. The Ca-HCO3 waters are the result of calcium carbonate dissolution, Na-HCO3 waters result from cation exchange and carbonate dissolution, while in the Na-ClSO4 and Na-Cl waters, mixing with connate and with encroached old marine water from the underlying and overlying sediments are the most relevant processes. The proposed values for the upper limit of the natural background consider the influence of geology and Holocene marine ingressions in the baseline of coastal groundwater. This study allowed to know the initial chemical conditions of the groundwater system of the Matanza-Riachuelo River basin and to establish the reference from which Basin Authority can start to evaluate trends and monitor the recovery plan. At the same time, it sets a precedent for future studies in the region.